2021
DOI: 10.34067/kid.0004432020
|View full text |Cite
|
Sign up to set email alerts
|

Association between Immunoglobulin M and Steroid Resistance in Children with Nephrotic Syndrome: A Retrospective Multicenter Study in Japan

Abstract: Background: The prognosis of steroid resistant nephrotic syndrome (SRNS) in children is poorer than steroid-sensitive cases. The diagnosis is made following the response to the initial 4-week corticosteroid therapy, which might be accompanied by side effects. However, predictive indicators at initial diagnosis remain unknown. We aimed to investigate whether selectivity index (SI) and other indicators at initial diagnosis, for example, serum immunoglobulin M (IgM) and total serum protein albumin ratio (TA ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Median age in the SRNS group was 10 years and in the SSNS group was 12.5 years with a minimum age of almost the same in both groups Also, Mortazavi and Khiavi (11) showed that there is no statistically difference between steroid resistant and steroid sensitive nephrotic children regarding to sex and age. In contrast Udagawa et al (2) showed that among 80 patients with idiopathic nephrotic syndrome, 13 patients (M:F = 5:8) with mean age 3.87 ± 3.27 were steroid-resistant and 67 patients (M:F = 47:20) were steroid-sensitive with mean age = 4.88 ± 3.98 years, with a statistical difference between steroid resistant and steroid sensitive nephrotic children regarding to sex and age (p< 0.05).…”
Section: Sd=standard Deviationmentioning
confidence: 86%
See 4 more Smart Citations
“…Median age in the SRNS group was 10 years and in the SSNS group was 12.5 years with a minimum age of almost the same in both groups Also, Mortazavi and Khiavi (11) showed that there is no statistically difference between steroid resistant and steroid sensitive nephrotic children regarding to sex and age. In contrast Udagawa et al (2) showed that among 80 patients with idiopathic nephrotic syndrome, 13 patients (M:F = 5:8) with mean age 3.87 ± 3.27 were steroid-resistant and 67 patients (M:F = 47:20) were steroid-sensitive with mean age = 4.88 ± 3.98 years, with a statistical difference between steroid resistant and steroid sensitive nephrotic children regarding to sex and age (p< 0.05).…”
Section: Sd=standard Deviationmentioning
confidence: 86%
“…Steroid resistance is often diagnosed as a failure to induce complete remission after 4 weeks of standard steroid therapy with 60 mg/m 2 intravenous or oral prednisolone per day. In accordance with the guidelines of the International Study of Kidney Disease in Children, complete remission is defined as a reduction in proteinuria to < 0.2 mg/mg protein-creatinine ratio in the first-morning urine void, or negative dipstick test results for three consecutive days (2) .…”
Section: Group (B): Included 24 Children With Steroid Sensitive Nephr...mentioning
confidence: 99%
See 3 more Smart Citations